An finite iterative algorithm for sloving periodic Sylvester bimatrix equations. Issue 15 (October 2020) - Zhang, Lei; Tang, Shiyu; Lv, Lingling
Abstract: The problem considered in this paper is to solve periodic Sylvester bimatrix equations. Based on the conjugate gradient method and least squares principle, an iterative algorithm is presented to solve the periodic Sylvester bimatrix equations. We show that the iterative solutions of the algorithm converge to the exact solutions at finite steps with any initial values. Finally, a numerical example is given to illustrate the validity and efficiency of the iterative algorithm.